Influence of the number of implants in the edentulous mandible on chewing efficacy and oral health‐related quality of life—A within‐subject design study - Passia, Nicole; Chaar, Mohammed Sad; Krummel, Anna; Nagy, Andreas; Freitag‐Wolf, Sandra; Ali, Shurouk; Kern, Matthias (Clinical oral implants research, 2022)
Objectives To investigate the chewing efficiency and oral health‐related quality of life of edentulous patients wearing complete dentures, successively supported by one, two, and three implants in the mandible. Methods Thirteen (13) edentulous patients of at least 50 years of age received three implants in the mandible. After a conventional submerged healing period, the central implant was uncovered and connected to the denture base using a stud attachment. Two months later, chewing efficacy was evaluated, and the two lateral implants were uncovered and connected to the denture base. The central retention element was replaced by a short healing abutment with no connection to the denture base. Chewing efficiency was evaluated two months later. Afterward, the healing abutment of the central implant was replaced by a stud attachment and again connected to the denture base. Two months later, chewing efficacy was evaluated again. Oral health‐related quality of life (OHRQoL) was measured at each recall visit using the summary score of the oral health impact profile. For statistical analysis of chewing efficacy, the changes from baseline (with no implants) to one, two, and three implants were used and tested by analysis of variance with repeated mesurements. Results Chewing efficacy clearly increased after implant loading, with a significant increase when two implants were loaded (p ≤ .05), compared to the chewing efficacy with no implants. OHRQoL also significantly improved after implant loading. Conclusions Within the limitations of the present clinical trial regarding the number of patients, chewing efficacy as well OHRQoL of edentulous patients improve after implant placement in the mandible, irrespective of the number of implants. The best chewing efficacy was achieved with two implants.